Studi Literatur Peran Filsafat Ekonomi Islam dalam Pengembangan Rasionalitas Pendidikan di Indonesia - Mhd. Rofi Febrian; Muhammad Anwar; Aflah Muhajir; Ahmad Wahyudi Zein (Lembaga Pengembangan Kinerja Dosen, 2025)
Through a literature review, this research investigates how Islamic economic theory has contributed to the rationalisation of education in Indonesia. An integrative education system that harmonises material and spiritual aspects is built on the principles of justice, balance and benefit. Therefore, Islamic economic philosophy provides a framework for moral and spiritual education that produces morally and intellectually strong people. In order to deal with globalisation and create a generation that is grounded in moral principles and thinks logically, this application is essential. To incorporate Islamic economic philosophy into national education policy and create a globally competitive education system that preserves regional spiritual and cultural values, curriculum design, teacher training and stakeholder participation are necessary.